ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA (STUDI KASUS DI DESA BUKIT KIJANG KECAMATAN NAMANG KABUPATEN BANGKA TENGAH TAHUN 2019) - Kusnia, Asi; Panjaitan, Fery; Medinal (Jurnal Akuntansi Bisnis Dan Keuangan, 2020)
This study aims to determine the accountability of the management of the Village Fund Allocation in Bukit Kijang Village, Namang District, Central Bangka Regency. The method used in this study is a qualitative research method with a descriptive analysis approach. The data used are secondary and primary data. Data collection techniques in this study used interviews and documentation. The formulation of the problem in this study is how to manage ADD accountability in Bukit Kijang Village, Namang District, Central Bangka Regency. The results of the study show that the accountability of Village Fund Allocation in Bukit Kijang Village physically has been going well according to applicable regulations with evidence of transparent accountability.